Impact of pandemia on demand by food delivery application in Piracicaba/SP (Research, Society and Development, 2021)
The arrival of the Covid-19 pandemic in the national territory brought about measures of restriction and isolation, factors that triggered changes in the consumption habits of the population. This work aims to analyze the increase in the demand for meal orders, between the pre-pandemic and pandemic year (between 2019 and 2020), in three different restaurants that provide ready-to-eat food through delivery from an application of purchase, in the Municipality of Piracicaba-SP. The focus is to analyze the demand behavior of orders based on the analysis of the evolution of three variables: i) number of orders placed; ii) total revenue in the periods; iii) and average purchase ticket. The data presented in the empirical research indicated an increase in the number of new orders, in total sales and in the average ticket in the three restaurants analyzed, when compared to the years 2019 and 2020, this growth was more evident in the case of restaurant A.